Fibrin-Platelet Clots in Acute Ischemic Stroke. Predictors and Clinical Significance in a Mechanical Thrombectomy Series - Hernández-Fernández, Francisco; Ramos-Araque, María E.; Barbella-Aponte, Rosa; Molina-Nuevo, Juan David; García-García, Jorge; Ayo-Martin, Oscar; Pedrosa-Jiménez, María José; López-Martinez, Lorena; Serrano-Heras, Gemma; Julia-Molla, Enrique; Segura, Tomás (Frontiers in Neurology, 2021)
Introduction The histological composition of the clot influences its mechanical properties, affects the efficacy of endovascular treatment (EVT) and could determine the clinical outcome of patients with acute ischemic stroke (AIS). Insights into clot composition may guide therapeutic decision-making prior to EVT and facilitate revascularization therapies. Material and Methods Consecutive patients with AIS recorded in a prospective single center reperfusion registry from December 2015 to December 2019 and treated with EVT were included. Baseline, laboratory (including post-procedural C-reactive protein [CRP]), radiological and angiographic variables were analyzed. We aimed to study the relationship between histological composition of the clot with basal neuroimaging, laboratory markers and recanalization technique. Secondary outcome was to analyze the correlation between clot composition and functional outcome at three months assessed by modified Rankin scale (mRS). Results From the study period 360 AIS patients treated with EVT were included, of whom 189 (53%) fulfilled inclusion criteria. One hundred (53%) cases of fibrin-predominant clot (FPC) were recorded. Full recanalization in FPC cases was achieved with higher probability when Stent Retrievers (SR) were selected as the first-line device (68.2%, p=0.039). Patients with FPC had higher levels of CRP (p=0.02), lower frequency of Hyperdense Middle Cerebral Artery (HMCA) in baseline imaging (p=0.039), and higher rates of mortality (p=0.012). The multivariate analysis showed that the absence of HMCA (OR=0.420; 95% CI 0.197-0.898; p=0.025) and higher levels of CRP (OR=1.01; 95% CI 1.003-1.019; p=0.008) were predictors of FPC. Leukocytes and platelet counts were not associated with clot histology. Conclusions The absence of HMCA and higher levels of CRP were markers of FPC. In patients with FPC, complete recanalization was most likely to be achieved when a SR was selected as first-line of treatment. Mortality was higher in patients within this histologic group.